Reconstruction optimization of distorted FeOOH/Ni hydroxide for enhanced oxygen evolution reaction. (July 2022) - Feng, Jinxian; Chen, Mingpeng; Zhou, Pengfei; Liu, Di; Chen, Yu-Yun; He, Bingchen; Bai, Haoyun; Liu, Dong; Ip, Weng Fai; Chen, Shi; Liu, Detao; Feng, Wenlin; et al.
Abstract: Oxygen evolution reaction (OER) is one of the most important anodic reactions in electrochemical conversion devices. Although a lot of OER electrocatalysts have been developed, the actual active sites during OER have not been fully understood. Herein, we report that the distorted FeOOH/Ni hydroxide on Ni foam (NF) (d-FeOOH/Ni hydroxide-NF) shows better electrochemical performance (1.50 V at 100 mA/cm 2 and long-term stability for 32 h at 425 mA/cm 2 ) than crystalline FeOOH/Ni hydroxide-NF (c-FeOOH/Ni hydroxide-NF) and outperforms most of the state-of-the-art electrocatalysts. By using in-situ and ex-situ techniques, we show that the interfaces in d-FeOOH/Ni hydroxide-NF, which are the key active sites for OER, are well maintained during the reaction, leading to promoted catalytic performance and long-term stability at high current density. We demonstrate that the structure rearrangement in d-FeOOH/Ni hydroxide-NF endows high flexibility of the lattice and tolerates the volume expansion during OER. Our study provides an insightful understanding on the catalytic performance of Fe-Ni-based electrocatalysts and the guidance to their design and synthesis for practical application. Graphical abstract: Image 1 Highlights: Distorted FeOOH/Ni hydroxide on Ni foam (NF) (d-FeOOH/Ni hydroxide-NF) shows high oxygen evolution reaction (OER) activity and stability at high current density. The structure rearrangement in d-FeOOH/Ni hydroxide-NF during OER results in high flexibility of the lattice, which tolerates the volume expansion. The FeOOH/Ni hydroxide interface of d-FeOOH/Ni hydroxide-NF is well maintained during OER.